Novel Subperiosteal Device Geometry and Investigation of Efficacy on Surrounding Bone Formation and Bone-Bonding Strength - Yoshiya Kaisaka; Masayoshi Uezono; Masaki Inoue; Kazuo Takakuda; Keiji Moriyama (Bioengineering)
To develop a safer bone-bonding device that promotes early osseointegration with cortical bone perforation, novel subperiosteal device geometries were proposed and evaluated for their ability to facilitate surrounding bone formation and enhance bone-bonding strength. This study used animal experiments and mechanical testing to assess the performance of these designs. The experimental device consisted of two main components: a rounded rectangular plate and a centrally positioned cylinder. To promote the recruitment of bone-marrow-derived factors, slits were incorporated into the cylinder, and a center hole was created directly above it. Four device variations, differing by the presence or absence of the slits and center hole, were fabricated and then subjected to tensile tests for mechanical property evaluation. In the animal experiments, the devices were bilaterally placed on rat tibiae, and after four weeks, bone-bonding strength tests were performed. Additionally, micro-computed tomography and histological analysis of undecalcified sections were conducted. All devices demonstrated early osseointegration, and geometric design differences, specifically the presence or absence of the slits and center hole, significantly affected the mechanical properties and bone induction. However, no significant differences in bone-bonding strength were detected. These findings suggest that the newly formed bone inside the slits and center hole contributes to the reinforcement of the device.